Assessment of green jobs in Dubai - Ulrike Lehr; Helena Walter (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2016)
This paper presents an assessment method for measuring green jobs in Dubai. Firstly, we describe the economic structure of Dubai and identify, which part of the economic sectors can be accounted for as green by international standards. Secondly, we describe the labor market in Dubai and assign the green economy's activities to the respective labor force. Finally we conclude with a comparison with the literature and an outlook on future development.
Keywords: 330; green jobs; labor market; green economy